2011
DOI: 10.1128/jcm.02139-10
|View full text |Cite
|
Sign up to set email alerts
|

The rs8099917 Polymorphism, When Determined by a Suitable Genotyping Method, Is a Better Predictor for Response to Pegylated Alpha Interferon/Ribavirin Therapy in Japanese Patients than Other Single Nucleotide Polymorphisms Associated with Interleukin-28B

Abstract: We focused on determining the most accurate and convenient genotyping methods and most appropriate single nucleotide polymorphism (SNP) among four such polymorphisms associated with interleukin-28B (IL-28B) in order to design tailor-made therapy for patients with chronic hepatitis C virus (HCV) patients. 4%) patients, the four SNPs were not in LD. Eight of nine (88.9%) patients whose rs8099917 was homozygous for the major allele were virological responders, even though one or more of the other SNPs were heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 24 publications
3
60
0
3
Order By: Relevance
“…The rs8099917 SNP is associated with treatment response in Asians with genotype 2HCV infections. 28,29 RFLP analysis yielded unambiguous genotypes for the rs8099917 SNP (Figure 1). The minor allele frequency (MAF) was 0.17 at rs8099917 (G allele).…”
Section: Genotypes At Rs8099917 Are Significantly Associated With Svrmentioning
confidence: 99%
See 1 more Smart Citation
“…The rs8099917 SNP is associated with treatment response in Asians with genotype 2HCV infections. 28,29 RFLP analysis yielded unambiguous genotypes for the rs8099917 SNP (Figure 1). The minor allele frequency (MAF) was 0.17 at rs8099917 (G allele).…”
Section: Genotypes At Rs8099917 Are Significantly Associated With Svrmentioning
confidence: 99%
“…We chose this SNP becauseit has been strongly associated with treatment response in an Asian genome-wide association study 17 The rs8099917 polymorphism has been found to be a better predictor of treatment response in Asiansthan other IL28B SNPs. 28 A recent study from Japan has shown that treatment response (both RVR: rapid virological response, defined as conversion to HCV-RNA test-negativity after 4 weeks of therapy and SVR) in a cohort of genotype 2 HCV-infected patients was significantly associated with rs8099917. 29 Other studies 30,31 have also demonstratedthe association of IL28B SNPs with SVR in genotype 2/3 HCV infections.…”
Section: Introductionmentioning
confidence: 99%
“…SNP rs12979860 (INFL3) was PCR-amplified from isolated genomic DNA with standard Taq polymerase (Inbio-Highway, Tandil, Argentina) [19] . The PCR-amplified fragments were bi-directionally sequenced using BigDye Termination chemistry system (Applied Biosystems, Life Technologies Corp., Foster City, CA, United States).…”
Section: Pre-treatment Characteristicsmentioning
confidence: 99%
“…IL28B and ITPA SNPs were not available for only two patients (1.2%). Although rs12979860, another IL28B SNP that is also strongly correlated to the therapeutic outcome, has been reported [15] , we determined only rs8099917 because it was previously reported that rs8099917 and rs12979860 represent 98.6% of the Japanese population [16] .…”
Section: Interleukin 28b and Inosine Triphosphate Pyrophosphatase Polmentioning
confidence: 99%
“…HCV RNA was tested at baseline, weeks 1, 2, 3, 4,6,8,12,16,20, and 24 during the treatment and at weeks 4,8,12, and 24 after the end of treatment. We defined the early stage of treatment as the period between day 1 and week 12.…”
Section: Clinical and Laboratory Assessmentmentioning
confidence: 99%